Clinical laboratory parameters in patients with COVID-19 - Naivy Sánchez Vera; Danay Saavedra Hernández; Carlos Jorge Hidalgo Mesa; Maykel Aguila López; Gladys Abreu Gutiérrez; Vivian Herrera González; Iliana Teresa Rodríguez García (Revista Cubana de Medicina Militar)
Introduction: Knowing the alterations in clinical laboratory tests is useful in the diagnosis and progress of patients with COVID-19. Objective: To describe the clinical laboratory parameters in patients diagnosed with COVID-19. Methods: Descriptive study in 82 hospitalized patients with COVID-19. The variables analyzed were age, sex, comorbidity, patient report, discharge status, hemoglobin, white blood cell count, absolute neutrophil count, absolute lymphocyte count, platelet count, erythrocyte sedimentation rate, D-dimer, creatinine, urea, alanine aminotransferase, aspartate aminotransferase, γ-glutamyl transpeptidase, alkaline phosphatase, lactate dehydrogenase, neutrophil / lymphocyte and platelet / lymphocyte ratio. Results: The average age was 55.61 ± 22.04, the majority were female (57.3%), hypertensive (41.5%), 18.3% reported serious and 14.6% died. Advanced age and comorbidity were associated with the severity report. There was a significant decrease in hemoglobin, lymphocytes; elevated erythrocyte sedimentation rate, D-dimer, creatinine, γ-glutamyl transpeptidase, and lactate dehydrogenase, especially in severe patients. The neutrophil / lymphocyte and platelet / lymphocyte ratio warned about the worsening of the patient and the possibility of death. Conclusions: The patients a mean age of 55.61, female, with arterial hypertension; they were discharged alive, reported as not serious. Mean hemoglobin values decrease, global lymphocyte count, especially in severe patients; increases D-dimer, creatinine, ALT, AST, ALP, GGT, and LD. The neutrophil / lymphocyte and platelet / lymphocyte ratio show high mean values, especially in severely ill patients and in those who died.